A comparison of growth impairment and orthodontic results in adult patients with clefts of palate and unilateral clefts of lip, palate and alveolus - G. Schultes,* A. Gaggl, H. Kärcher (Blackwell Synergy, 2000)
Many authors have described the influence on facial growth of the operation for correction of cleft lip, palate, and alveolus.1–8 Overall formation and development of the maxilla according to the type of cleft have therefore been analyzed extensively.